2017
DOI: 10.3892/etm.2017.4854
|View full text |Cite
|
Sign up to set email alerts
|

Blood purification treatment initiated at the time of sepsis diagnosis effectively attenuates serum HMGB1 upregulation and improves patient prognosis

Abstract: The aim of the present study was to investigate the increase in serum and urine levels of high mobility group box protein 1 (HMGB1) during sepsis and the effect of blood purification treatments on HMGB1 levels and patient prognosis. A total of 40 intensive care patients with sepsis were randomly assigned to different groups (n=10 per group): A control group (sepsis group), a continuous renal replacement treatment (CRRT) group, a hemoperfusion (HP) group and an HP+CRRT group. The blood purification treatments u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Two trials had four treatment arms. 43,58 Twenty trials used a hemoperfusion technique, 13 used hemofiltration or hemodiafiltration, 4 trials combined hemofiltration with hemoperfusion, and 2 trials used plasma exchange. In three cases we received further information from corresponding authors.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Two trials had four treatment arms. 43,58 Twenty trials used a hemoperfusion technique, 13 used hemofiltration or hemodiafiltration, 4 trials combined hemofiltration with hemoperfusion, and 2 trials used plasma exchange. In three cases we received further information from corresponding authors.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Gibot et al[ 30 ] (2007) demonstrated that serum HMGB1 levels greater than 4000 pg/mL (4 ng/mL) on the third evaluation day patients with septic shock were associated with a higher risk of death, with an odds ratio equal to 5.5 and ranging from 1.3-23.6 considering the 95% confidence interval. However, as occurred in the current study, the authors found no significant association between HMBG1 and the clinical and laboratory parameters that make up the SOFA score when these were assessed separately[ 30 , 31 ]. Other authors have failed to demonstrate an association between serum HMGB1 levels and patient survival in other clinical situations[ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 48%
“…Table 1), and the mean age was 59 years. Twenty-one studies started treatment within 24 h of sepsis diagnosis [9, 19, 36, 37, 41, 44-46, 48-53, 56, 58, 60, 62, 65, 68, 69]. In the other studies, treatment was initiated up to 6 days from diagnosis of sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…These included 2,729 patients, of whom 1,393 (51%) were randomized to the treatment arm (online suppl. [49,68], and 1 used plasma exchange [36].…”
Section: Study Characteristicsmentioning
confidence: 99%